Common genetic variants related to vitamin D status are not associated with esophageal squamous cell carcinoma risk in China. Issue 2 (April 2015) - Wang, Jian-Bing; Dawsey, Sanford M.; Fan, Jin-Hu; Freedman, Neal D.; Tang, Ze-Zhong; Ding, Ti; Hu, Nan; Wang, Le-Min; Wang, Chao-Yu; Su, Hua; Qiao, You-Lin; Goldstein, Alisa M.; et al.
Highlights We evaluated the association between 12 vitamin D-related-SNPs and ESCC risk using data from a GWAS. None of the 12 evaluated SNPs in the four vitamin D-related genes were significantly associated with risk of ESCC. Our study provides the first evaluation of common genetic variants in vitamin D-related genes and risk of ESCC.